Contextual-Based E-Book on Balinese Script Writing Learning Materials - Maharani, Alifia; Suniasih, Ni Wayan (MIMBAR PGSD Undiksha, 2022)
The lack of interactive teaching materials used to support Balinese language learning activities causes students to lack understanding of the material and be less interested in learning the Balinese language. This study aims to create teaching materials in the form of a contextual-based e-book suitable for fourth-grade elementary school students. This study uses the ADDIE development model, which consists of 5 stages, analysis, design, development, implementation, and evaluation. The types of data collected in this study are quantitative data and qualitative data. The subjects in this study were one subject matter expert, one learning design expert, one learning media expert, and 12 elementary school fourth-grade students. The method of data collection uses the questionnaire method. The teaching material in the form of this e-book is declared eligible by obtaining the percentage results from the subject matter expert test with very good qualifications (95%), the learning design expert test with very good qualifications (91.7%), the learning media expert test with very good qualifications (90 %), individual trials with good qualifications (85%), and small group trials with good qualifications (88.8%). It can be concluded that the contextual-based e-book on the local content of writing Balinese script for the fourth grade is declared feasible to be used in the Balinese language learning process.